Top answers

Maths
A Level

Express the following in partial fractions: (1+2x^2)/(3x-2)(x-1)^2

(1+2x^2)/(3x-2)(x-1)^2 = -5/x-1 + 3/(x-1)^2 + 17/3x-2

Answered by Manny S. Maths tutor
3436 Views

let p be a polynomial p(x) = x^3+b*x^2+ c*x+24, where b and c are integers. Find a relation between b and c knowing that (x+2) divides p(x).

We know that (x+2) divides p(x), therefore p(x) can be written as p(x) = (x+2)q(x) + 0, where q is another polynomial of degree 2. We can calculate then p(-2): p(-2)= ((-2)+2)q(-2) = 0;p(-2)= (-2)...

Answered by Tina-Alina S. Maths tutor
3313 Views

Find the radius and centre of the circle given x^2+4x+y^2+2y=20

Complete the square:x2+4x gives (x+2)2-4y2+2y gives (y+1)2 -1Therefore,(x+2)2-4+(y+1)2 -1=20Rearranging gives:(x+2)2+(y+1)...

Answered by Stanley C. Maths tutor
3224 Views

How can I find all the solutions to cos(3x) = sqrt(2)/2 for 0<=x<=2pi ?

Finding the solutions to trig equations begins in a very similar way to when we do it at GCSE. We start with:cos(2x) = 2-1/2 0 <= x <=piand correct our range, as we are interested in 2x n...

Answered by Thomas U. Maths tutor
6495 Views

Finding the tangent of an equation using implicit differentiation

y2e2x = 3y + x21) Differentiation: Product rule, Explicity differentiation.2) Rearrangement: Collecting terms, Making dy/dx subject.

Answered by Paul J. Maths tutor
3169 Views

We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences